Alcohol and Marijuana Use and Intentions Among Adolescents: The Role of the Reasoned Action Approach and Positive Future Orientation. Issue 6 (September 2018) - Stoddard, Sarah A.; Pierce, Jennifer
Perceptions of alcohol and other drug (AOD) use are associated with adolescent substance use behavior, yet research on the role of contextual factors and positive assets in this relationship is scant. This study examined the relationship between school environment and peer influence and past 30-day alcohol and marijuana use via positive future orientation and AOD perceptions in a high school sample ( n = 392; 49% male; 73% White). A positive peer influence and a positive school environment were associated with lower alcohol and marijuana use via future orientation, reasoned action approach (RAA) constructs (i.e., injunctive norms, AOD expectancies, and perceived control over AOD use), and intentions to avoid AOD use. The findings provide support for the role of a positive future orientation in the prevention of AOD use among youth and point to differential paths of influence for contextual factors.